Personal Deixis in literary texts: Religious texts for the third year secondary school as a case study - mabrouk, hamza; lehouimel, badis (El Omda in Linguistics and Discourse Analysis, 2023)
The pragmatic research is based on multiple mechanisms for studying linguistic discourse, and among these mechanisms there are deixis. The communication process between the speaker and the addressee cannot be done without the presence of these deixis; Personal, Temporal, and Spatial one. This study aims to determine the pragmatics of personal deixis, and questioning its structure, patterns, semantic value, and intentions through the contexts to which it is linked. This is done through literary texts, specifically religious one for third year high school. The research focus on the roles played by these personal deixis in achieving the process of reporting and communication through these texts as a model for personal deixis